2009
DOI: 10.2460/javma.235.10.1181
|View full text |Cite
|
Sign up to set email alerts
|

Use of phenol red thread tests to evaluate tear production in clinically normal Amazon parrots and comparison with Schirmer tear test findings

Abstract: Results indicated that the PRTT and STT were both viable methods for measurement of tear production in Hispaniolan Amazon parrots. Topical application of an ophthalmic anesthetic agent did not have a significant effect on the PRTT values but significantly decreased the STT values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 19 publications
7
58
7
2
Order By: Relevance
“…The values found by these authors were higher (12.3±4.5mm/ min) compared to parrots. Storey et al (2009) described values of 7.9±2.6 and 5.1±3.3mm/min for STT-1 and STT-2, respectively, evaluating A. ventralis parrots, where the values obtained for STT-1 were above those measured for A. aestiva. Methodological modifications certainly affect the results obtained and should be considered in the interpretation of the findings, besides anatomic and physiologic characteristics of the species studied.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The values found by these authors were higher (12.3±4.5mm/ min) compared to parrots. Storey et al (2009) described values of 7.9±2.6 and 5.1±3.3mm/min for STT-1 and STT-2, respectively, evaluating A. ventralis parrots, where the values obtained for STT-1 were above those measured for A. aestiva. Methodological modifications certainly affect the results obtained and should be considered in the interpretation of the findings, besides anatomic and physiologic characteristics of the species studied.…”
Section: Discussionmentioning
confidence: 75%
“…Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009). …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some investigators have used the phenol red thread (PRT) tear test for measuring tear production in birds. 6,14 The PRT tear test is an alternative method of tear measurement by which tear production is measured using a 75-mm-long cotton thread that has been impregnated with 1 ll of phenolsulfonphthalein, a pH-sensitive indicator. When the more alkaline tears are absorbed, the pH indicator turns the thread from yellow to red.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,15 The wide range of normal STT values in avian species justifies the importance of determining baseline values for individual species and demonstrates the risk of extrapolating normal values from one species to another. 10 The mean STT values in the present study were 16.3 6 2.5 mm/1 min when measurements from both eyes were averaged.…”
Section: Discussionmentioning
confidence: 99%